Saba Banana (Musa balbisiana) Peels, Smooth Cayenne Pineapple (Ananas comosus) Leaves, and Tomato (Solanum lycopersicum) Seeds as 3-Layer Eco-Friendly Face Masks - Lee, Irish Yi-Fung M (Animo Repository, 2023)
This study determined the effectiveness of saba banana (Musa balbisiana) peels, smooth cayenne pineapple (Ananas comosus) leaves, and tomato (Solanum lycopersicum) seeds in producing eco-friendly and plantable face masks. This study was conducted because of the increasing plastic waste due to disposable face masks. The researchers examined and compared the durability and filtration abilities of eco-friendly and disposable face masks using water absorption, water repellency, optical microscopy analysis, and tensile strength test. The eco-friendly masks had a high tensile strength compared to disposable masks. It also passed the other testing methods conducted in the study. Therefore, the researchers concluded that these eco-friendly masks could be an alternative to disposable masks.